IMPLEMENTASI PENGGUNAAN ALAT EDUKASI KARTU BERGAMBAR (FLASH CARD) DALAM MENINGKATKAN KEMAMPUAN BAHASA INGGRIS SISWA - Lubis, Muya Syaroh Iwanda; Rahim, Rani; Nasution, Asrindah; Nurhayati, Nurhayati; Anggraini, Putri; Sartika, Dwi (LPPM Universitas Nusa Mandiri, 2023)
Students' interest in learning English is still low, which means students' English language skills are also low. This is because during the learning process in the classroom, teachers do not use learning media such as educational tools. Educational tools are very important if applied in learning. This is because educational tools can increase students' learning motivation so that learning is more meaningful, innovative and creative. Therefore, the service team carries out service activities regarding the use of educational tools in classroom learning. This service activity aims to increase students' interest in learning and also students' English language skills. This service activity was carried out at MIS Nurul Hidayah Medan. Participants in this activity were class V students consisting of 30 students. This activity will be carried out on September 6 2023. This activity will be carried out in 3 stages. The first stage is to give a pretest to students before carrying out implementation activities using picture card educational tools (flash cards). The second stage is implementing the use of flash cards in English lessons. The third stage is giving a posttest to students after carrying out implementation activities using picture card educational tools (flash cards). The results of this activity were that the student response was very good and students were more interested in learning using the flash card educational tool and there was an increase in student ability obtained from the N-Gain score which was in the medium category. So it can be concluded that the flash card educational tool can improve students' English language skills.